Determination of moisture content in mortar at near relaxation frequency 17 GHz - Jusoh, Mohamad Ashry; Abbas, Zulkifly; Lee, Kim Yee; You, Kok Yeow; Md Norimi, Amizadillah (Sciendo, 2011)
The knowledge of moisture content in cement based material is important especially for the safety in field work. In this paper, a non-destructive and contactless free space method is used for measurement of moisture content in cement based materials (mortar) at microwave frequencies. The measurement system consists of a 17 GHz dielectric resonator oscillator (DRO) as a microwave source, a Power Meter as the detector, and a pair of lens horn antennas to transmit and receive the microwave signal. An empirical formula of moisture content was obtained by using a relationship between attenuation and moisture content. This model is best for prediction of moisture content greater than 2% with percentage mean error of 3%.